2017
DOI: 10.17219/acem/68578
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of thrombosis for patients with essential thrombocythaemia: A single center study

Abstract: Background. Thrombotembolic complications are the leading cause of mortality in essential thrombocythemia (ET), but the definition of thrombotic risk remains far from clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These studies investigated relationship between MPV, JAK2 mutational status and history of thrombosis with inconsistent findings among studies. Only one work reported statistically significant result for MPV and history of thrombosis in ET [29]. Similarly, higher MPV was associated with JAK2 mutation in two studies [31,32], whereas result did not reach statistical significance or was not tested in other.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These studies investigated relationship between MPV, JAK2 mutational status and history of thrombosis with inconsistent findings among studies. Only one work reported statistically significant result for MPV and history of thrombosis in ET [29]. Similarly, higher MPV was associated with JAK2 mutation in two studies [31,32], whereas result did not reach statistical significance or was not tested in other.…”
Section: Discussionmentioning
confidence: 95%
“…We identified six previous studies [21,22,[29][30][31][32] assessing role of MPV in Ph-MPN patients (PMF patients comprised a minority of analyzed populations in two works [21,22] and were not included in other studies). These studies investigated relationship between MPV, JAK2 mutational status and history of thrombosis with inconsistent findings among studies.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition to the above mentioned thrombotic risk factors, there are additional factors that contribute to the increased risk of thrombosis: leukocytosis and leuko-trombocyte aggregates, P selectin expression and granulocyte tissue factor, increase mean platelet volume. 19,20 In the evaluation of the important thrombotic risk to be assessed, there are also the presence of thrombophilia, the qualitative changes in platelets and the degree of expression of the platelet derived micro particles. Non-cirrhotic, non-malignant portal vein thrombosis, not associated with acute abdominal inflammation or abdominal surgery, is often due to thrombophilia.…”
Section: Factorsmentioning
confidence: 99%
“…However, not all studies have shown the importance of the presence of these mutations in increasing the risk of thrombophilia. 20 It seems to be important only the association of the presence of Factor V Leiden that increases the risk of thrombotic complications. 24 Platelet has a very important role in the occurrence of thrombotic complications.…”
Section: Factorsmentioning
confidence: 99%
“…ET is associated with an increased risk of thrombosis and/or haemorrhage, as well as progression to myelofibrosis (Passamonti et al , ; Barbui, ). The most important risk factors include previous thromboembolic events, age >60 years, and JAK2 V617F mutation (Barbui et al , ; Prajs & Kuliczkowski, ). Cytoreductive therapy is recommended for these patients (Barbui et al , ).…”
mentioning
confidence: 99%